Coordinated Plasticity of Synapses and Astrocytes Underlies Practice-Driven Functional Vicariation in Peri-Infarct Motor Cortex - Soo Young Kim; J. Edward Hsu; Lincoln C. Husbands; Jeffrey A. Kleim; Theresa A. Jones (2017)
Motor rehabilitative training after stroke can improve motor function and promote topographical reorganization of remaining motor cortical movement representations, but this reorganization follows behavioral improvements. A more detailed understanding of the neural bases of rehabilitation efficacy is needed to inform therapeutic efforts to improve it. Using a rat model of upper extremity impairments after ischemic stroke, we examined effects of motor rehabilitative training at the ultrastructural level in peri-infarct motor cortex. Extensive training in a skilled reaching task promoted improved performance and recovery of more normal movements. This was linked with greater axodendritic synapse density and ultrastructural characteristics of enhanced synaptic efficacy that were coordinated with changes in perisynaptic astrocytic processes in the border region between head and forelimb areas of peri-infarct motor cortex. Disrupting synapses and motor maps by infusions of anisomycin (ANI) into anatomically reorganized motor, but not posterior parietal, cortex eliminated behavioral gains from rehabilitative training. In contrast, ANI infusion in the equivalent cortical region of intact animals had no effect on reaching skills. These results suggest that rehabilitative training efficacy for improving manual skills is mediated by synaptic plasticity in a region of motor cortex that, before lesions, is not essential for manual skills, but becomes so as a result of the training. These findings support that experience-driven synaptic structural reorganization underlies functional vicariation in residual motor cortex after motor cortical infarcts. SIGNIFICANCE STATEMENT Stroke is a leading cause of long-term disability. Motor rehabilitation, the main treatment for physical disability, is of variable efficacy. A better understanding of neural mechanisms underlying effective motor rehabilitation would inform strategies for improving it. Here, we reveal synaptic underpinnings of effective motor rehabilitation. Rehabilitative training improved manual skill in the paretic forelimb and induced the formation of special synapse subtypes in coordination with structural changes in astrocytes, a glial cell that influences neural communication. These changes were found in a region that is nonessential for manual skill in intact animals, but came to mediate this skill due to training after stroke. Therefore, motor rehabilitation efficacy depends on synaptic changes that enable remaining brain regions to assume new functions.